Three of a Kind: Control of the Expression of Liver-Expressed Antimicrobial Peptide 2 (LEAP2) by the Endocannabinoidome and the Gut Microbiome - Mélissa Shen; Claudia Manca; Francesco Suriano; Nayudu Nallabelli; Florent Pechereau; Bénédicte Allam-Ndoul; Fabio Arturo Iannotti; Nicolas Flamand; Alain Veilleux; Patrice D. Cani; Cristoforo Silvestri; Vincenzo Di Marzo (Molecules, 2021)
The endocannabinoidome (expanded endocannabinoid system, eCBome)-gut microbiome (mBIome) axis plays a fundamental role in the control of energy intake and processing. The liver-expressed antimicrobial peptide 2 (LEAP2) is a recently identified molecule acting as an antagonist of the ghrelin receptor and hence a potential effector of energy metabolism, also at the level of the gastrointestinal system. Here we investigated the role of the eCBome-gut mBIome axis in the control of the expression of LEAP2 in the liver and, particularly, the intestine. We confirm that the small intestine is a strong contributor to the circulating levels of LEAP2 in mice, and show that: (1) intestinal Leap2 expression is profoundly altered in the liver and small intestine of 13 week-old germ-free (GF) male mice, which also exhibit strong alterations in eCBome signaling; fecal microbiota transfer (FMT) from conventionally raised to GF mice completely restored normal Leap2 expression after 7 days from this procedure; in 13 week-old female GF mice no significant change was observed; (2) Leap2 expression in organoids prepared from the mouse duodenum is elevated by the endocannabinoid noladin ether, whereas in human Caco-2/15 epithelial intestinal cells it is elevated by PPARγ activation by rosiglitazone; (3) Leap2 expression is elevated in the ileum of mice with either high-fat diet—or genetic leptin signaling deficiency—(i.e., ob/ob and db/db mice) induced obesity. Based on these results, we propose that LEAP2 originating from the small intestine may represent a player in eCBome- and/or gut mBIome-mediated effects on food intake and energy metabolism.